Antenatally detected thoracic lesions: Prognosis, management and outcome - Md Mokarram Ali; Nilesh Tank; Monika Bawa (Wolters Kluwer Medknow Publications, 2024)
Background: Foetal thoracic lesions are uncommon, with the incidence of 1 in 15,000 live births. Antenatal monitoring of these lesions is required to prognosticate the parents about the postnatal outcome of the lesions and about the well-being of the baby. Foetal ultrasound and magnetic resonance imaging (MRI) are the modalities to detect these lesions and follow-up during pregnancy and postnatally. Congenital pulmonary adenomatoid malformations (CPAM), congenital diaphragmatic hernia (CDH) and bronchopulmonary sequestrations (BPS) are the commonly detected foetal thoracic lesions. Parameters such as congenital cystic adenomatoid malformation (CCAM) volume ratio (CVR) and lung-to-head ratio (LHR) determine the prognosis of these lesions. With this background, we planned to study the prognosis and outcome of antenatally detected thoracic lesions. Materials and Methods: This was a prospective study carried out for 2 years (January 2017 to December 2018). Pregnant females with foetuses diagnosed to have thoracic lesions on the second- and third-trimester ultrasound and foetal MRI were enrolled for the study. CVR and LHR were noted. Outcomes were analysed in terms of the need of termination of pregnancy, foetal or neonatal demise and need of surgery or conservative management. Results: Of a total of 521 pregnancies, thoracic lesions were detected in 22 (4.22%) cases. Individually, the incidence of each lesion was: CPAM-10 (45.45%), BPS-5 (22.73%), CDH-5 (22.73%) and congenital higher airway obstruction-2 (9.1%). Chromosomal screening was normal in 100% of cases. Follow-up was done for 2 years. Termination of pregnancy was required in 3 (13.64%) cases, postnatal death occurred in 4 (18.2%) cases, surgery was required in three cases of CDH soon after birth and two cases of extralobar BPS at 2 years of age. 10 (45.45%) cases were managed conservatively, who are doing well at 2-year follow-up. Conclusion: CPAMs, BPSs and CDH are the commonly detected antenatal thoracic lesions. Ultrasonography and MRI help detect and prognosticate the parents about the outcomes of these lesions. CVR and LHR with associated congenital malformations are important prognostic markers for these lesions. There is a need of long-term prospective studies to delineate the natural history of these lesions.